PENGARUH MOTIVASI DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA GURU SD NEGERI DI JAWAI - Rinto, .; M. Amin,, Maswardi.; ., M. Chiar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe purpose of observation is to know effect of motivation to work and organization culture to job satisfaction elementary school teacher in Jawai subdistrict. This observation is use quantitative with descriptive analytic method. Population in this observation is PNS?s teaacher in elementary school Jawai subdistrict were 179 techers  with amount of sample 124 teachers. Data were collected using a questionnaire with measurement models using Likert scale. The collected data is tabulated. Then analyzed with the help of a computer application program, SPSS version 20 for Windows. Base on the result of observation is that (1) to get effect of motivation to work (X1) to job satisfaction teacher (Y) with beta (b1) is 0, 422 = 42,2%; (2) to get effect of organization culture (X2) to get job satisfaction teacher (Y) with beta (b1) is 0,520 = 52,0%; (3) to get effect of motivation to work (X1) and organization culture (X2) to job satisfaction teacher (Y) looked from R Square is 33,6%. The result test F that to see output ANOVA from analysis double regression linier to show that F count > F table (26,854 > 3,07).Key word: Motivation, Organization Culture, Job Satisfaction.